The management operating procedures based on Surah Al-Fatihah: A preliminary review - Abdul Hakim, Abdullah; Ahmad Azrin, Adnan; Rohaizan, Baru (2016)
Surah al-Fatihah is the essence of the Qu’ran and a guide for the muslims to perform their duty as servants and caliphs on earth. Therefore, they must embrace the principles and values contained in surah al-Fatihah. Although the Islamic management method is recognised as comprehensive and progressive, it has failed to convince leaders in many Islamic countries and Islamic institutions to apply it as a system. Similarly, in the context of academic research, the existing western-oriented management frameworks are used even for studying Islamic-related issues. This is because the existing western management methods are more widely accepted and internationally recognised, while the existing Islamic management methods are, in fact, very limited. This paper attempts to present a preliminary study on Islamic-based management operating procedures derived from surah al-Fatihah as a contribution towards developing Islamic management concept and method. This qualitative study used content analysis as the instrument for collecting data. This analysis involved surah al-Fatihah, translation of the surah written by Abdullah Yusuf Ali, hadith and interpretation of the surah by mufassirin to represent Islamic views on the subject matter. This study found that among the management operating procedures and principles based on surah al-Fatihah are reciting basmalah, loving and caring, working not for personal interest, be proactive, managing risks, working as ‘ibadah, implementing du’a’, teamwork, following the right track and avoiding fraud. These procedures and principles should be practised by muslim leaders as their management operating procedures in order to develop a strong concept of Islamic management, to produce managers with integrity, good characters and skills as well as to create management as an effort of achieving success (al-falah) in the world and the hereafter.